A Comparative Study of Physical and Digital Communication as Perceived by Humanities and Social Sciences Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
When people are physically separated, such as during the COVID-19 pandemic, they aremore likely to use digital communication to replace in-person interactions. However, thepersistence of digital inequality suggests that, during a public health crisis, not everyone willbe equally capable or inclined to increase digital communication.The purpose of this study is to be able to choose the best form of communication to employ indaily interactions, meetings at work, and interpersonal interactions, as well as how it benefitsus.Nowadays, many people use digital communication because it is easier and faster, but ourstudies show that the use of physical communication is better than digital communicationbecause it is clearer and avoids wrongly gathering information.
Keywords: Education